Ethnographic views of Brazil’s (new) authoritarian turn - Neiburg, Federico; Thomaz, Omar Ribeiro (HAU journal of ethnographic theory, 2020)
In this introduction to Currents, we argue for the potential of ethnography to aid in understanding the present. Extended periods of fieldwork allow anthropologists that are in the field well before the facts—that is, before significant political events occur—to provide unique frameworks for understanding those events, frameworks that can incorporate conjuncture as it is lived by the subjects in the sceneries being researched into analysis that take into account more long-term processes. Focusing on the current political conjuncture in Brazil and placing it in a comparative perspective, we explore the peculiar position that anthropologists of contemporary Brazil occupy, in which their role in the production of knowledge and their participation in public debates makes them a target for the conservative and reactionary wave that is engulfing the country.